Novel Two‐Dimensional Porous Materials for Electrochemical Energy Storage: A Minireview. Issue 9 (2nd July 2020) - Mao, Lei; Zhao, Xun; Wang, Huayu; Xu, Hong; Xie, Li; Zhao, Chenglan; Chen, Lingyun
Abstract: Two dimensional (2D) porous materials have great potential in electrochemical energy conversion and storage. Over the past five years, our research group has focused on Simple, Mass, Homogeneous and Repeatable Synthesis of various 2D porous materials and their applications for electrochemical energy storage especially for supercapacitors (SCs). During the experimental process, through precisely controlling the experimental parameters, such as reaction species, molar ratio of different ions, concentration, pH value of reaction solution, heating temperature, and reaction time, we have successfully achieved the control of crystal structure, composition, crystallinity, morphology, and size of these 2D porous materials including transition metal oxides (TMOs), transition metal hydroxides (TMHOs), transition metal oxalates (TMOXs), transition metal coordination complexes (TMCCs) and carbon materials, as well as their derivatives and composites. We have also named some of them with CQU‐Chen (CQU is the initialism of Chongqing University, Chen is the last name of Lingyun Chen), such as CQU‐Chen‐Co−O‐1, CQU‐Chen‐Ni−O−H‐1, CQU‐Chen‐Zn−Co−O‐1, CQU‐Chen‐Zn−Co−O‐2, CQU‐Chen‐OA−Co‐2‐1, CQU‐Chen‐Co−OA‐1, CQU‐Chen‐Ni−OA‐1, CQU‐Chen‐Gly−Co‐3‐1, CQU‐Chen‐Gly−Ni‐2‐1, CQU‐Chen‐Gly−Co−Ni‐1, etc. The introduction of 2D porous materials as electrode materials for SCs improves the energy storage performances. These materials provide a large number of active sites for ion adsorption, supply plentiful channels for fast ion transport and boost electrical conductivity and facilitate electron transportation and ion penetration. The unique 2D porous structures review is mainly devoted to the introduction of our contribution in the 2D porous nanostructured materials for SC. Finally, the further directions about the preparation of 2D porous materials and electrochemical energy conversion and storage applications are also included. Abstract : 2D porous materials have great potential in electrochemical energy storage and conversion. In this minireview, we have highlighted recent progresses on simple, mass, homogeneous and repeatable synthesis of various 2D porous materials including transition metal‐base materials and their derivatives and composites in our group and their applications for electrochemical energy storage especially for SCs.